Hyperplastic and fibrosing gastropathy resembling Ménétrier disease in a cat - Barker, Emi N (JFMS Open Rep, 2019)
CASE SUMMARY: A 3.5-year-old domestic shorthair cat presented with a 6 month history of weight loss and polyphagia. Clinical examination revealed a markedly reduced body condition score (2/9) and a quiet demeanour. Laboratory abnormalities comprised a mild non-regenerative anaemia, stress leukogram, hypoproteinaemia due to hypoalbuminaemia, azotaemia, hypokalaemia, total hypocalcaemia and sub-maximally concentrated urine (specific gravity 1.020). Abdominal ultrasonography revealed marked thickening of the gastric mucosa within the fundus, body and pylorus; the most dorsal portion of the fundus was spared. The thickened mucosa contained multiple small, anechoic cyst-like structures. The gastric submucosa, muscularis and serosa appeared normal. Histopathology, performed on a full-thickness gastric biopsy, revealed mucosal hypertrophy and markedly dilated gastric glands in areas; not all gastric glands were affected, with some appearing normal or atrophic. Focal interstitial fibrosis was present in some areas. The findings of hypoproteinaemia, gastric ultrasonographic changes and histopathology results share several similarities to those reported with Ménétrier disease. RELEVANCE AND NOVEL INFORMATION: Ménétrier disease is a rare condition of the stomach in humans. A similar condition, giant hypertrophic gastritis (or Ménétrier-like disease), has also been described rarely in dogs. To our knowledge, Ménétrier-like disease has not been previously described cats. This case shares features of Ménétrier-like disease, raising the suspicion of a similar aetiopathogenesis.